Dopaminergic modulation of reward discounting in healthy rats: a systematic review and meta-analysis. - Castrellon, Jaime J.; Meade, James; Greenwald, Lucy; Hurst, Katlyn; Samanez-Larkin, Gregory R. (Psychopharmacology, 2021)
Rationale: Although numerous studies have suggested that pharmacological alteration of the dopamine (DA) system modulates reward discounting, these studies have produced inconsistent findings. Objectives: Here, we conducted a systematic review and pre-registered meta-analysis to evaluate DA drug-mediated effects on reward discounting of time, probability, and effort costs in studies of healthy rats. This produced a total of 1343 articles to screen for inclusion/exclusion. From the literature, we identified 117 effects from approximately 1549 individual rats. Methods: Using random effects with maximum-likelihood estimation, we meta-analyzed placebo-controlled drug effects for (1) DA D1-like receptor agonists and (2) antagonists, (3) D2-like agonists and (4) antagonists, and (5) DA transporter-modulating drugs. Results: Meta-analytic effects showed that DAT-modulating drugs decreased reward discounting. While D1-like and D2-like antagonists both increased discounting, agonist drugs for those receptors had no significant effect on discounting behavior. A number of these effects appear contingent on study design features like cost type, rat strain, and microinfusion location. Conclusions: These findings suggest a nuanced relationship between DA and discounting behavior and urge caution when drawing generalizations about the effects of pharmacologically manipulating dopamine on reward-based decision-making.